Cost-Effectiveness of BRCA 1/2 Genetic Test and Preventive Strategies: Using Real-World Data From an Upper-Middle Income Country - Lourenção, Marina; Simões Correa Galendi, Julia; Galvão, Henrique de Campos Reis; Antoniazzi, Augusto Perazzolo; Grasel, Rebeca Silveira; Carvalho, André Lopes; Mauad, Edmundo Carvalho; Oliveira, Jorge Henrique Caldeira de; Reis, Rui Manuel; Mandrik, Olena; Palmero, Edenir Inêz (Frontiers in Oncology, 2022)
Although the BRCA 1/2 genetic testing in developed countries is part of the reality for high-risk patients for Hereditary Breast and Ovarian Cancer (HBOC), the same is not true for upper-middle-income countries. For that reason, this study aimed to evaluate whether the BRCA1/2 genetic test and preventive strategies for women at high-risk for HBOC are cost-effective compared to not performing these strategies in an upper-middle-income country. Adopting a payer perspective, a Markov model with a time horizon of 70 years was built to delineate the health states for a cohort of healthy women aged 30 years that fulfilled the BRCA1/2 testing criteria according to the guidelines. Transition probabilities were calculated based on real-world data of women tested for BRCA 1/2 germline mutations in a cancer reference hospital from 2011 to 2020. We analysed 275 BRCA mutated index cases and 356 BRCA mutation carriers that were first- or second-degree relatives of the patients. Costs were based on the Brazilian public health system reimbursement values. Health states utilities were retrieved from literature. The BRCA1/2 genetic test and preventive strategies result in more quality-adjusted life years (QALYs) and costs with an incremental cost-effectiveness ratio of R$ 11,900.31 (U$ 5,504.31)/ QALY. This result can represent a strong argument in favor of implementing genetic testing strategies for high-risk women even in countries with upper-middle-income, considering not only the cancer prevention possibilities associated with the genetic testing but also its cost-effectiveness to the health system. These strategies are cost-effective, considering a willingness-to-pay threshold of R$ 25,000 (U$ 11,563.37)/QALY, indicating that the government should consider offering them for women at high-risk for HBOC. The results were robust in deterministic and probabilistic sensitivity analyses.